SISTEM PAKAR DIAGNOSIS PENYAKIT KULIT MENGGUNAKAN METODE FORWARD CHAINING DENGAN PYTHON - Siahaan, Ranty Deviana (Jurnal Informatika dan Teknik Elektro Terapan, 2024)
Abstract. Skin is the outer layer of the body that functions to protect the inside. Like other parts of the body, the skin is also susceptible to disorders or diseases. Currently, the need for healthy skin is increasing due to pollution, free radicals and hot weather. Increased awareness about the importance of healthy skin encourages people to pay more attention to skincare. However, delays in identifying the type of disease and lack of knowledge about prevention can lead to more severe skin conditions, such as cancer. An expert system is an information system that utilizes knowledge and decision-making methods from experts in a particular field. Therefore, the author developed a system to help people with early diagnosis of skin diseases using the forward chaining method and the Python programming language. This implementation succeeded in creating an expert system capable of diagnosing skin diseases using the forward chaining method and Python. Based on testing each existing rule, the expert system succeeded in providing a diagnosis, description, solution or medicine, as well as a picture of the disease based on the symptoms reported by the user.